A Three-Component Decomposition of the Change in Relative Poverty: An Application to China - Zengzeng Fan; Wei Zou (Land, 2023)
China has eliminated absolute poverty and begun to tackle relative poverty, yet the change in relative poverty in China has been less studied. In this paper, we develop a three-component decomposition of the change in relative poverty and apply it to analyze the relative poverty in China. The change in relative poverty is decomposed into identification, growth, and redistribution components. We compare the three-component decomposition with other decomposition methods in the existing literature and show the advantages of the former. Our study, using the China Family Panel Studies (CFPS) 2010–2018 data, shows that relative poverty is rising. Examining the periods of 2012–2014, 2014–2016, and 2016–2018, we show that the three components differ in their contribution to relative poverty. The identification component rises with income growth and increases relative poverty by 8.42%, 12.19%, and 12.55%, respectively. The growth component reduces the incidence of relative poverty by 8.34%, 11.24%, and 12.18%, respectively. In comparison, the redistribution component increases the incidence of relative poverty by 2.88%, 1.12%, and 6.60%, respectively.